Estrutura cristalográfica da lectina de sementes da Canavalia maritima Aub, em complexo com o ácido gamaaminobutírico (GABA) e a adenina revela novas características estruturais e prediz mecanismo anti-herbivoria - Silva Filho, José Caetano da (2013)
Plants are sessile organisms susceptible to biotic and abiotic stresses. Insect herbivore attacks are factors that affect their survival and development. To defend themselves, plants produce and release chemical compounds, such as non protein amino acids, that negatively affect the development processes of their attackers, as well as use phytohormones that regulate defense responses against herbivory. In the present work, we seek to understand in depth the insecticidal activity related to ConM, a lectin isolated from beach bean seeds (Canavalia maritima Aub.), through their crystal structure analysis in complex with the non protein amino acid GABA (gamma-aminobutyric acid) and adenine, a nitrogen base-precursor of cytokinins, phytohormones involved in defense responses against insect herbivores. In this way, we co-crystallized ConM with GABA and soaked the derived crystals into an adenine 5mM solution. It was viewed through ConM monomeric model that GABA stabilization occurs through interactions displayed with amino acid residues that participate in the coordination of its isomer alpha-aminobutyric acid (Abu). In the other hand, adenine molecule displays interactions with amino acid residues from ConM Carbohydrate Recognition Domain due ahydrophobic pocket adjacently localized to this ligand-binding site and formed from a secondary non repetitive structure of β-bulge. A dimeric model of ConM reveals that lectin insecticidal activity is related to conformational changes of Gln132, resulting in GABA release without quaternary structure change. Hence, the presented results might contribute to greater understanding of lectins interactions with different chemical ligands, helping their application as biotechnological tools.